The endogeneity of the natural rate of growth for a selection of Asian countries - Mark Dray; A. P. Thirlwall (University of Kent, School of Economics, 2010)
The paper questions the assumption in all of mainstream growth theory that the Harrod natural rate of growth is exogenously determined and independent of the pressure of demand in an economy. First a simple statistical technique is presented for estimating the natural rate of growth, and then it is shown how it is possible to test for its endogeneity. The model is applied to ten Asian countries, and the results support the conclusions from previous studies of OECD and Latin American countries that the natural rate of growth is elastic to the actual rate of growth working through induced labour supply and productivity growth. Demand matters for economic growth.
Keywords: O4; O5; 330; demand-led growth; endogenous labour supply and productivity growth; Asia